2019
DOI: 10.1109/access.2019.2927880
|View full text |Cite
|
Sign up to set email alerts
|

An Accurate Numerical Algorithm for Attitude Updating Based on High-Order Polynomial Iteration

Abstract: To effectively improve the accuracy of attitude reconstruction under highly dynamic environments, a new numerical attitude updating algorithm is designed in this paper based on the high-order polynomial iteration according to the differential equation for quaternion. In this algorithm, a high-order polynomial is introduced to fit the angular rate accurately without increasing the number of gyro outputs during per attitude updating interval. This algorithm can provide an exact high-order polynomial solution for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Studies have shown that the last truncation error is small enough and can be neglected when qðNh,0Þ is determined by the sum of the first N þ 3 terms in (8). 20 Consequently, the key to reduce QPI error is to improve the fitting precision of the angular rate, and the ideal case occurs when δω¼ 0.…”
Section: Brief Review Of Qpi Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the last truncation error is small enough and can be neglected when qðNh,0Þ is determined by the sum of the first N þ 3 terms in (8). 20 Consequently, the key to reduce QPI error is to improve the fitting precision of the angular rate, and the ideal case occurs when δω¼ 0.…”
Section: Brief Review Of Qpi Algorithmmentioning
confidence: 99%
“…Combining ( 2), ( 9), (29), and (30), the Picard series solutions to Qð4hÞ are directly solved. 20 However, there exist potential problems that limit the precision of quaternion reconstruction. To be specific, the process of constructing the three-degree polynomial in (29) involves the computation of the Moore-Penrose pseudoinverse of matrix, which means that c 0 4 and c 0 5 are the minimum-norm solution of and c 0 5 , it is convinced that the substitution of À3=5c 2 × c 3 and 1=5c 2 × c 3 for c 1 × c 0 4 and c 0 × c 0 5 in the process of calculating qð4h,0Þ is beneficial to design high-precision four-sample attitude updating algorithm.…”
Section: Quaternion Reconstruction By Higher Degree Polynomialmentioning
confidence: 99%